The influence of green innovative products on brand love: The intermediary effect of perceived uniqueness and brand acceptance and the moderating effect of green social responsibility——A case study of new energy vehicles - Zhang, Yu; Chen, Sze Ting (Edelweiss Applied Science and Technology, 2025)
This study investigates the impact of innovative green products on brand love, focusing on the mediating roles of perceived uniqueness and brand acceptance, and the moderating effect of green social responsibility. Using stratified random sampling, 1,667 questionnaires were distributed among consumers familiar with green automotive innovations. Structural Equation Modeling (SEM) was employed to analyze the interrelationships among variables. Findings reveal that green innovative products positively influence brand love, with perceived uniqueness and brand acceptance significantly mediating this relationship. Additionally, green social responsibility moderates the strength of these mediating effects, either enhancing or weakening the emotional bond depending on consumer alignment with environmental values. The study provides empirical evidence that innovation and consumers’ perception of uniqueness and acceptance shape emotional attachment to green brands. The novelty of this research lies in its integrated model that combines dual mediators and a moderator within the context of new energy vehicle brands, offering new insights into brand loyalty development in sustainability-driven markets. The results suggest that brands should emphasize product uniqueness and foster consumer acceptance to enhance emotional connection while aligning green social responsibility initiatives with consumer values to reinforce brand love. These findings offer practical and theoretical guidance for marketers and enterprises aiming to optimize green innovation strategies, build stronger consumer-brand relationships, and enhance long-term brand loyalty in the context of sustainable development.